Electrochemical Impedance Response of Zn and Galvanized Steel Corroding under Marine Atmospheric Environments - Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2009)
Impedance response of zinc and galvanized steel samples exposed in wet-dry cyclic condition using 0.05 M NaCl solution has been analyzed in order to evaluate their corrosion behavior. The wet-dry cyclic test was performed by exposing sample to alternate conditions of 1 h immersion in 0.05 M NaCl solution and 7 h drying at 298 K with relative humidity (RH) of 60% for 10 days consisting of 30 cycles. After initial exposure to corrosion test, samples showed the evolution of two capacitive loops. However, a sharp decrease of characteristic frequency, characterized by an increase of double layer capacitance in the rage of several mF/cm2, with the progress of corrosion was observed. This was explained by taking into account the coupling of characteristic frequencies of the two capacitive loops due to deposition of thick layer of porous rust. The parameters of diffusion impedance for the cathodic process were estimated from the low frequency capacitive loops attributed to finite Warburg diffusion impedance. A sharp increase of impedance after several days of corrosion in the case of galvanized steel was attributed to the dissolution of Fe-Zn alloy layer that is formed during galvanizing process. Keywords: galvanized steel, zinc, atmospheric corrosion, wet-dry cyclic test. DOI: 10.3126/jncs.v23i0.2094 J. Nepal Chem. Soc., Vol. 23, 2008/2009 page: 33-42